POLITICAL PARTIES ESSENCE IN UKRAINIAN POLITICAL MARKET FRAMEWORK - Работягова, І.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article reviews the Ukrainian political parties’ essence, non-implementation of functions correspondent to them, realization of which causes status and role characteristics of organization as a political party in the political market. The functioning features of Ukrainian party organizations in political market framework give the reason to consider them as party substitutes, which not just carry out the power and social building function but also withstand the progressive political parties building.